Role of 1-MCP in regulating 'Kensington Pride' mango fruit softening and ripening - Razzaq, K.; Singh, Zora; Khan, A.; Khan, Shamim Ahmed Kamal Uddin; Ullah, S. (Springer, 2016)
Ripening of mango fruit is characterized by softening of flesh which limits its shelf life. 1-MCP is nontoxic gas that delays fruit softening and improves quality of several fruit. Therefore, the role of 1-MCP in regulating fruit softening and quality of ‘Kensington Pride’ mango was investigated. Physiological mature fruits treated with 1-MCP (1 mL L-1), ethylene (10 mL L-1) or 1-MCP + ethylene for 12 h at ambient condition (20 ± 1 C). Untreated (control) as well as treated fruits were allowed to ripe at ambient temperature (20 ± 1 C) for 10 days. Ethylene production, respiration rate and other fruit ripening parameters were determined periodically. Climacteric peaks of ethylene production and respiration rate were significantly supressed by 1-MCP application as compared to ethylene-treated and control fruit. Exogenous application of ethylene accelerated the development of fruit colour, fruit softening with increased activities of exo-PG, endo-PG and EGase enzymes in the pulp tissues. Whereas, activities of fruit softening enzymes were significantly delayed and/or suppressed in 1-MCP-treated fruit. 1-MCP-treated fruit showed improved rheological properties (i.e., firmness, springiness and stiffness), decreased level of citric acid, malic acid, succinic acid, total organic acids, total sugars and sucrose than other treatments. 1-MCP inhibited the activities of fruit softening enzymes which consequently delayed the ripening and ripening related changes in ‘Kensington Pride’ mango.